KONVERSI SELULOSA TANDAN KOSONG SAWIT (TKS) MENJADI ETANOL - Rakhman Sarwono; Eka Triwahyuni; Yosi Aristiawan; Hendris Hendarsyah Kurniawan; Trisanti Anindyawati (JURNAL SELULOSA, 2014)
A serious global energy crisis is thought to be originated from the imbalance rapid consumption and the non-renewable nature of the fossil fuels. A potential, yet promising route for diminising this problem might involve rapid conversion of organic waste and biomass into fuels as an alternative. Oil-palm empty fruit bunch (EFB) is the waste from the oil palm plantation which abundant amount of lignocellulosic EFB biomass. EFB biomass was used as raw material of the second generation of bioethanol production. EFB was converted into ethanol through enzymatic hydrolysis and fermentation simultaneously. Cellulose waste was then turned into glucose by enzymatic saccharification and finally fermented into ethanol. The experiment of 20 liter broth resulted in ethanol concentration of about 7.93% (w/w). Conversion of cellulose into glucose was about 60.02%, and conversion of glucose into ethanol was about 88.44%. Following distillation, ethanol of 1970 mL was obtained at a concentration of 63% (v/v).Keywords: EFB, saccharification, fermentation, glucose, ethanol  ABSTRAKAdanya krisis energi minyak bumi secara global disebabkan oleh ketimpangan antara konsumsi dan produksi minyak bumi. Guna mengimbangi ketimpangan tersebut, maka dilakukan konversi limbah organik dan biomassa menjadi bahan bakar secara tepat dan cepat. Tandan Kosong Sawit (TKS) merupakan limbah dari perkebunan sawit yang melimpah jumlahnya. Penelitian etanol generasi kedua berbahan baku biomassa lignoselulosa dilakukan melalui proses sakarifikasi selulosa menjadi glukosa secara enzimatis dan fermentasi glukosa menjadi etanol. Berdasarkan hasil yang diperoleh dari 20 liter hidrolisat didapat konsentrasi etanol sebesar 7,93% (b/b). Hasil konversi selulosa menjadi glukosa sebesar 60,02%, sedangkan konversi glukosa menjadi etanol sebesar 88,44%. Setelah dilakukan distilasi didapatkan etanol sebanyak 1970 mL dengan konsentrasi 63% (v/v).Kata kunci: TKS, sakarifikasi, fermentasi, glukosa, etanol